2000
DOI: 10.1159/000026664
|View full text |Cite
|
Sign up to set email alerts
|

(±)3,4-Methylenedioxymethamphetamine (‘Ecstasy’)-Induced Serotonin Neurotoxicity: Studies in Animals

Abstract: The popular recreational drug, (±)3,4-methylenedioxymethamphetamine (MDMA; ‘Ecstasy’) is a potent and selective brain serotonin (5-HT) neurotoxin in animals. MDMA-induced 5-HT neurotoxicity can be demonstrated using a variety of neurochemical, neuroanatomical and, more recently, functional measures of 5-HT neurons. Although the neurotoxic effects of MDMA in animals are widely accepted, the relevance of the animal data to human MDMA users has been questioned, largely because dosages of drugs used in animals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
193
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(204 citation statements)
references
References 35 publications
6
193
0
5
Order By: Relevance
“…246 These acute effects are followed by a temporary attenuation of central 5-HT. 247 There is evidence to indicate that MDMA has neurotoxic effects on the 5-HTergic system in animals 248 and humans, 249,250 mainly characterized by a decreased number of serotonin transporters. 249,251 Animal studies have indicated that MDMA administration results in long-term attenuation of brain 5-HT and 5-HIAA as well as attenuated TPH activity and reductions in the density of 5-HT uptake sites (for review see Curran et al 252 ) and there is evidence to indicate that recovery may remain incomplete for several years.…”
Section: 4-methylenedioxymethamphetamine (Mdma)mentioning
confidence: 99%
“…246 These acute effects are followed by a temporary attenuation of central 5-HT. 247 There is evidence to indicate that MDMA has neurotoxic effects on the 5-HTergic system in animals 248 and humans, 249,250 mainly characterized by a decreased number of serotonin transporters. 249,251 Animal studies have indicated that MDMA administration results in long-term attenuation of brain 5-HT and 5-HIAA as well as attenuated TPH activity and reductions in the density of 5-HT uptake sites (for review see Curran et al 252 ) and there is evidence to indicate that recovery may remain incomplete for several years.…”
Section: 4-methylenedioxymethamphetamine (Mdma)mentioning
confidence: 99%
“…In addition to the acute effects of MDMA to enhance monoamine and ACh release, it is well documented that the repeated administration of MDMA results in a long-term reduction in brain tissue concentrations of 5-HT and reductions in 5-HT reuptake sites in rodents and nonhuman primates (c.f., Ricaurte et al, 2000;Green et al, 2003;Gudelsky and Yamamoto, 2003). On the basis of these neurochemical effects, MDMA is generally viewed to be selectively neurotoxic to 5-HT terminals.…”
Section: Long Term Effects Of Repeated Mdma Administrationmentioning
confidence: 99%
“…The popularity of this drug has given rise to concern, since preclinical research has demonstrated that repeated doses of MDMA can cause serotonergic neurodegeneration in animals (eg Ricaurte et al, 1992Ricaurte et al, , 2000Steele et al, 1994;Green et al, 1995), and there is some evidence that chronic consumption of ecstasy is associated with protracted dysregulation of 5-HT systems in humans. Drug-free ecstasy users have been found to have low levels of 5-HT, and its metabolite 5-HIAA Kish et al, 2000).…”
Section: Introductionmentioning
confidence: 99%